Method for improving strength and long-term service performance of brazed joint in skutterudite thermoelectric device by using cobalt-based barrier layer
By using a cobalt-based barrier layer in the square cobalt-based thermoelectric devices, the problems of performance attenuation and low brazed joint strength in the existing technology Chinese square cobalt-based thermoelectric devices during long-term service are solved, and higher joint strength and longer service performance are achieved.
Patent Information
- Application Number
- CN202411830073.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-12
AI Technical Summary
During the long-term service of existing thermoelectric devices, there are problems of performance attenuation and low brazing joint strength, resulting in the growth of the interface reaction layer, increase in contact resistance and attenuation of thermoelectric performance.
A cobalt-based barrier layer is used to uniformly grind the cobalt powder and the refractory metal powder and integrated hot press sintering with the square cobalt ore powder to form a preset barrier layer, thereby inhibiting element diffusion and alleviating interface stress during the brazing process.
It effectively inhibits the diffusion of Sb elements, reduces the growth of the interface reaction layer, improves the shear strength of the brazed joints, and extends the long-term service performance of square cobalt ore thermoelectric devices.
Smart Images

Figure CN119501221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoelectric material connection, and in particular relates to a method for improving the strength and long-term service performance of a brazed joint in a skutterudite thermoelectric device. Background Art
[0002] Thermoelectric devices are semiconductor energy conversion devices with great application potential that can realize the mutual conversion of thermal energy and electrical energy. The service temperature of skutterudite thermoelectric devices is 300℃~600℃, which is a representative of medium-temperature thermoelectric devices. Skutterudite thermoelectric devices are often used in deep space exploration in the aerospace field. For example, the Curiosity Mars rover and the Cassini Saturn rover are equipped with skutterudite thermoelectric devices. Skutterudite thermoelectric devices convert the heat generated by nuclear reactors into electrical energy, thereby realizing the use of nuclear energy to power aircraft for a long time.
[0003] During the manufacturing process of skutterudite thermoelectric devices, electrodes and multiple skutterudite thermoelectric legs need to be brazed and then packaged into devices. There are two problems with the existing brazing technology of skutterudite and electrodes. The first is the attenuation of performance after long-term service. Skutterudite thermoelectric devices are often used in environments that require long-term service, such as deep space exploration. The continuous diffusion of elements between skutterudite and electrodes will lead to the continuous growth of the interface reaction layer, the continuous increase of contact resistance, and the continuous attenuation of thermoelectric performance. The second is the low strength of the brazed joint. Skutterudite thermoelectric devices are subjected to repeated thermal shocks during service. The skutterudite and electrodes will expand and contract to varying degrees, resulting in greater stress at the interface. If the brazing bonding strength between the skutterudite and the electrode is insufficient, the device will crack or even break.
[0004] In summary, in order to obtain high-strength skutterudite thermoelectric devices that can be used for a long time, there are two requirements for the brazing of skutterudite and electrodes. First, the interface reaction layer should be as thin as possible, which requires the diffusion of barrier elements. Second, the joint strength should be high, which requires the relief of interface stress. How to make the brazed joint meet the above two requirements is the key prerequisite for the large-scale application of skutterudite thermoelectric devices. Summary of the invention
[0005] In order to solve the problems of poor long-term serviceability and low strength of brazed joints in existing skutterudite-electrode brazing, the present invention proposes a method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices by using a cobalt-based barrier layer.
[0006] The method of the present invention for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices by using a cobalt-based barrier layer is carried out in the following steps:
[0007] Step 1: Put cobalt powder and refractory metal powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0008] The barrier layer powder is formed by mixing cobalt powder and refractory metal powder, and the mass fraction of the cobalt powder in the barrier layer powder is 50% to 98%;
[0009] The refractory metal powder is one or more of tungsten powder, molybdenum powder, niobium powder and tantalum powder;
[0010] Step 2: pouring the skutterudite powder into a graphite mold, then spreading a layer of barrier layer powder on the skutterudite powder, and then transferring it to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a preset barrier layer;
[0011] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 1 kPa, then filling argon gas to a pressure of 50 to 100 kPa in the hot pressing furnace, then applying a pressure of 50 to 70 MPa, heating to 700 to 800° C. and keeping the temperature for 5 to 20 minutes, and finally cooling to 100 to 200° C.;
[0012] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0013] The solder is a Cu-based solder;
[0014] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, heat up to 600-700°C at a heating rate of 5-20°C / min for 5-20min, and then decrease to 100-200°C at a rate of 2-10°C / min.
[0015] The principles and beneficial effects of the present invention are:
[0016] 1. The element diffusion between skutterudite and the electrode is mainly the diffusion of the Sb element in the skutterudite into the electrode. After the present invention adds a cobalt-based barrier layer between the skutterudite and the electrode, since the components of the cobalt-based barrier layer are cobalt and refractory metals, the refractory metals have a high melting point, large bond energy, and high diffusion activation energy, the diffusion of the Sb element through the barrier layer into the electrode is inhibited.
[0017] 2. The components of the cobalt-based barrier layer in the present invention are cobalt and refractory metals. The thermal expansion coefficient of cobalt is greater than that of skutterudite, and the thermal expansion coefficient of refractory metals is less than that of skutterudite. The cobalt-based barrier layer is formed by sintering powder, so the components of the cobalt-based barrier layer can be flexibly adjusted, and the thermal expansion coefficient of the barrier layer is easy to match that of skutterudite. In addition, the barrier layer powder and the skutterudite powder are integrated by hot pressing and sintering, and a staggered interface is formed between the powders, which can well relieve the interface stress.
[0018] The CoMo barrier layer used in the existing method of connecting skutterudite thermoelectric materials and electrodes is a foil, and then the CoMo foil and skutterudite powder are hot-pressed and sintered, and the surface of the barrier layer is etched with grooves to achieve a roughening treatment to avoid stress concentration and increase the path for cracks to expand along the interface direction. The present invention integrates the barrier layer powder and the skutterudite powder for hot-pressing and sintering, and can directly obtain a low-stress interface between the barrier layer and the skutterudite, eliminating the step of surface roughening treatment. In terms of inhibiting the diffusion of the Sb element, since the CoMo foil is obtained by the arc melting process, the arc melting process has a fast cooling rate, and the grain size of the obtained CoMo foil is tens to hundreds of nanometers; while the grain size of the barrier layer of the present invention is equivalent to the powder particle size, that is, a few microns to tens of microns. Therefore, the barrier layer of the present invention contains fewer grain boundaries, because the grain boundary diffusion rate of atoms is much higher than the intracrystalline diffusion. The barrier layer of the present invention can better inhibit the diffusion of the Sb element because it contains fewer grain boundaries.
[0019] 3. The present invention can obtain a high-strength skutterudite thermoelectric device that can be used for a long time. In terms of long-term service performance, the present invention has confirmed the feasibility of long-term service for the first time by means of annealing treatment experimental results. The thickness of the interface reaction between skutterudite and the cobalt-based barrier layer is only 15 μm, and the thickness of the reaction layer only increases to 39 μm after annealing at 550°C for 10 days. In terms of strength, the shear strength of the brazed joint between the skutterudite and the electrode obtained by the present invention reaches 33.6 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Yb in the brazed joint obtained in Example 1 0.3 4Sb 12 Photo of the interface structure with the CoNb barrier layer;
[0021] Figure 2 Yb after annealing in Example 1 0.3 4Sb 12 Photo of the interface structure with the CoNb barrier layer;
[0022] Figure 3 Yb in the brazed joint obtained in Example 3 0.3 4Sb 12 Photo of the interface structure with the CoMo barrier layer. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0024] Specific implementation method 1: In this implementation method, the method of using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0025] Step 1: Put cobalt powder and refractory metal powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0026] The barrier layer powder is formed by mixing cobalt powder and refractory metal powder, and the mass fraction of the cobalt powder in the barrier layer powder is 50% to 98%;
[0027] The refractory metal powder is one or more of tungsten powder, molybdenum powder, niobium powder and tantalum powder;
[0028] Step 2: pouring the skutterudite powder into a graphite mold, then spreading a layer of barrier layer powder on the skutterudite powder, and then transferring it to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a preset barrier layer;
[0029] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 1 kPa, then filling argon gas to a pressure of 50 to 100 kPa in the hot pressing furnace, then applying a pressure of 50 to 70 MPa, heating to 700 to 800° C. and keeping the temperature for 5 to 20 minutes, and finally cooling to 100 to 200° C.;
[0030] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0031] The solder is a Cu-based solder;
[0032] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, heat up to 600-700°C at a heating rate of 5-20°C / min for 5-20min, and then decrease to 100-200°C at a rate of 2-10°C / min.
[0033] This embodiment has the following beneficial effects:
[0034] 1. The element diffusion between skutterudite and the electrode is mainly the diffusion of the Sb element in the skutterudite into the electrode. In this embodiment, after a cobalt-based barrier layer is added between the skutterudite and the electrode, since the components of the cobalt-based barrier layer are cobalt and refractory metals, the refractory metals have a high melting point, large bond energy, and high diffusion activation energy, thereby inhibiting the diffusion of the Sb element through the barrier layer into the electrode.
[0035] 2. In this embodiment, the components of the cobalt-based barrier layer are cobalt and refractory metals. The thermal expansion coefficient of cobalt is greater than that of skutterudite, and the thermal expansion coefficient of refractory metals is less than that of skutterudite. The cobalt-based barrier layer is formed by sintering powders, so the components of the cobalt-based barrier layer can be flexibly adjusted, and the thermal expansion coefficient of the barrier layer can easily match that of skutterudite. In addition, the barrier layer powder and the skutterudite powder are integrated by hot pressing and sintering, and a staggered interface is formed between the powders, which can well relieve the interface stress.
[0036] The CoMo barrier layer used in the existing method of connecting the skutterudite thermoelectric material and the electrode is a foil, and then the CoMo foil and the skutterudite powder are hot-pressed and sintered, and the surface of the barrier layer is etched with grooves to achieve a roughening treatment to avoid stress concentration and increase the path for cracks to expand along the interface direction. In this embodiment, the barrier layer powder and the skutterudite powder are hot-pressed and sintered as an integrated whole, and a low-stress interface between the barrier layer and the skutterudite can be directly obtained, eliminating the step of surface roughening. In terms of inhibiting the diffusion of the Sb element, since the CoMo foil is obtained by the arc melting process, the arc melting process has a fast cooling rate, and the grain size of the obtained CoMo foil is tens to hundreds of nanometers; while the grain size of the barrier layer of this embodiment is equivalent to the powder particle size, that is, a few microns to tens of microns. Therefore, the barrier layer of this embodiment contains fewer grain boundaries, because the grain boundary diffusion rate of atoms is much higher than the intracrystalline diffusion. The barrier layer of this embodiment can better inhibit the diffusion of the Sb element because it contains fewer grain boundaries.
[0037] 3. This embodiment can obtain a high-strength skutterudite thermoelectric device that can be used for a long time. In terms of long-term service performance, this embodiment has confirmed the feasibility of long-term service for the first time by means of annealing treatment experimental results. The thickness of the interface reaction between skutterudite and the cobalt-based barrier layer is only 15 μm, and the thickness of the reaction layer only increases to 39 μm after annealing at 550°C for 10 days. In terms of strength, the shear strength of the brazed joint between the skutterudite and the electrode obtained in this embodiment reaches 33.6 MPa.
[0038] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the ball milling step described in step 1 is: put cobalt powder, refractory metal powder, grinding balls, and anhydrous ethanol into a ball mill jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then ball mill for 6 to 24 hours under atmospheric environment. After the ball milling is completed, put it in a drying oven for drying.
[0039] Specific implementation method 3: This implementation method is different from specific implementation methods 1 or 2 in that: the chemical formula of the skutterudite in step 2 is R x Co y Fe 4-y Sb 12 , R is one or more of alkali metals, alkaline earth metals, rare earth metals, and elements of the third main group, 0<x≤1, 0≤y≤4.
[0040] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: in the integrated hot pressing sintering step in step 2, the heating rate is 80-150° C. / min, and the cooling rate is 5-50° C. / min.
[0041] Specific implementation mode 5: This implementation mode is different from any one of specific implementation modes 1 to 4 in that: the mass of the barrier layer powder in step 2 is 5% to 25% of the skutterudite powder.
[0042] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the electrode in step 3 is a metal electrode or an alloy electrode.
[0043] Specific implementation method seven: This implementation method is different from specific implementation method six in that: the material of the metal electrode is Cu, Ni, Fe, Co or Cr.
[0044] Specific implementation eight: This implementation differs from specific implementation six in that the alloy electrode is a Cu-based alloy, a Ni-based alloy, a Fe-based alloy, a Co-based alloy or a Cr-based alloy.
[0045] Specific embodiment nine: This embodiment differs from specific embodiment six in that: the Cu-based alloy is CuW or CuMo; the Ni-based alloy is NiW, NiMo or NiCr; the Fe-based alloy is FeW, FeMo, FeCr or FeCoNi; the Co-based alloy is CoW, CoMo, CoCr, CoNi or CoFe; the Cr-based alloy is CrW, CrMo, CrCoNi or CrFeNi.
[0046] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that: the grinding method described in step three is to grind step by step with 800-3000 mesh sandpaper; the polishing method is to polish on a polishing cloth with a diamond polishing agent with a particle size of 0.5-2.5 μm; the cleaning method is to rinse with acetone or anhydrous ethanol, and then ultrasonically clean in acetone or anhydrous ethanol for 5-30 minutes, and finally air-dry.
[0047] Example 1
[0048] The method of this embodiment using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0049] Step 1: Put Co powder and Nb powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0050] The mass ratio of the Co powder to the Nb powder is 8:2;
[0051] The ball milling step is as follows: Co powder, Nb powder, grinding balls and anhydrous ethanol are placed in a ball milling jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then the ball milling is carried out for 12 hours under an atmospheric environment, and the ball milling is carried out after the ball milling is completed, and the ball milling is carried out in a drying oven for drying;
[0052] Step 2: Yb 0.3 4Sb 12 The powder is poured into a graphite mold and then 0.3 4Sb 12 A layer of barrier layer powder is spread on the powder, and then the powder is transferred to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a pre-set barrier layer;
[0053] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 0.5 kPa, then filling argon gas to a pressure of 80 kPa in the hot pressing furnace, then applying a pressure of 60 MPa, heating to 750° C. and keeping the temperature for 10 minutes, and finally cooling to 150° C.;
[0054] The heating rate in the integrated hot pressing sintering step is 120°C / min and the cooling rate is 20°C / min;
[0055] The mass of the barrier layer powder is 20% of the skutterudite powder;
[0056] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0057] The electrode is a Cu electrode;
[0058] The grinding method is to grind with 800 mesh, 1500 mesh and 3000 mesh sandpaper in sequence; the polishing method is to polish with a diamond polishing agent with a particle size of 2.5 μm on a polishing cloth; the cleaning method is to rinse with anhydrous ethanol, then ultrasonically clean in anhydrous ethanol for 10 minutes, and finally air-dry;
[0059] The solder is CuSnP solder; CuSnP solder is a commercial solder with a liquidus temperature of 600-700°C;
[0060] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, the temperature was increased to 675 °C at a heating rate of 10 °C / min for 10 min, and then decreased to 200 °C at a rate of 5 °C / min.
[0061] Figure 1 Yb in the brazed joint obtained in Example 1 0.3 4Sb 12Interface structure photo with CoNb barrier layer; Yb 0.3 4Sb 12 The interface with CoNb is well bonded, with no defects such as cracks, indicating that the thermal expansion coefficients match well. The thickness of the surface reaction layer is only 15 μm, indicating that the CoNb barrier layer has a good effect in blocking element diffusion. The brazed joint was annealed at 550 ° C for 1, 2, 4, and 10 days, respectively. Figure 2 The Yb after annealing is shown 0.3 4Sb 12 Photo of the interface structure with the CoNb barrier layer; the thickness of the corresponding interface reaction layer was 22μm, 30μm, 34μm and 39μm respectively when the brazed joint was annealed at 550℃ for 1, 2, 4 and 10 days. The 550℃ annealing treatment is used to simulate the service environment of skutterudite. According to the thickness corresponding to different annealing times, it can be found that the thickness increases more and more slowly with time and approaches a limit. According to the relevant theories of non-equilibrium thermodynamics, it is predicted that the limit thickness of the interface reaction layer of the joint obtained in this embodiment is less than 100μm, which meets the use requirements. This shows that the cobalt-based barrier layer can effectively suppress the problems of continuous diffusion of elements and continuous growth of the reaction layer during long-term service, and is a feasible method to obtain skutterudite thermoelectric devices that can be used for a long time.
[0062] After testing, the Yb obtained by using the CoNb barrier layer in this embodiment 0.3 4Sb 12 The shear strength of the joint in the thermoelectric device is 33.6MPa, which meets the mechanical performance requirements of the thermoelectric device.
[0063] Example 2
[0064] The method of this embodiment using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0065] Step 1: Put Co powder and Nb powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0066] The mass ratio of the Co powder to the Nb powder is 7:3;
[0067] The ball milling step is as follows: Co powder, Nb powder, grinding balls and anhydrous ethanol are placed in a ball milling jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then the ball milling is carried out for 12 hours under an atmospheric environment, and the ball milling is carried out after the ball milling is completed, and the ball milling is carried out in a drying oven for drying;
[0068] Step 2: Yb 0.3 4Sb 12 The powder is poured into a graphite mold and then 0.3 4Sb 12A layer of barrier layer powder is spread on the powder, and then the powder is transferred to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a pre-set barrier layer;
[0069] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 0.5 kPa, then filling argon gas to a pressure of 80 kPa in the hot pressing furnace, then applying a pressure of 60 MPa, heating to 750° C. and keeping the temperature for 10 minutes, and finally cooling to 150° C.;
[0070] The heating rate in the integrated hot pressing sintering step is 120°C / min and the cooling rate is 20°C / min;
[0071] The mass of the barrier layer powder is 20% of the skutterudite powder;
[0072] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0073] The electrode is a Cu electrode;
[0074] The grinding method is to grind with 800 mesh, 1500 mesh and 3000 mesh sandpaper in sequence; the polishing method is to polish with a diamond polishing agent with a particle size of 2.5 μm on a polishing cloth; the cleaning method is to rinse with anhydrous ethanol, then ultrasonically clean in anhydrous ethanol for 10 minutes, and finally air-dry;
[0075] The solder is CuSnP solder; CuSnP solder is a commercial solder with a liquidus temperature of 600-700°C;
[0076] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, the temperature was increased to 675 °C at a heating rate of 10 °C / min for 10 min, and then decreased to 200 °C at a rate of 5 °C / min.
[0077] After testing, the Yb obtained by using the CoNb barrier layer in this embodiment 0.3 4Sb 12 The shear strength of the brazed joint of the thermoelectric device is 28.4MPa, which meets the mechanical performance requirements of the thermoelectric device.
[0078] Example 3
[0079] The method of this embodiment using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0080] Step 1: Put Co powder and Mo powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0081] The mass ratio of the Co powder to the Mo powder is 7:3;
[0082] The ball milling step is as follows: Co powder, Mo powder, grinding balls and anhydrous ethanol are placed in a ball milling jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then the ball milling is carried out for 12 hours under an atmospheric environment, and the ball milling is carried out after the ball milling is completed, and the ball milling is carried out in a drying oven for drying;
[0083] Step 2: Yb 0.3 4Sb 12 The powder is poured into a graphite mold and then 0.3 4Sb 12 A layer of barrier layer powder is spread on the powder, and then the powder is transferred to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a pre-set barrier layer;
[0084] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 0.5 kPa, then filling argon gas to a pressure of 80 kPa in the hot pressing furnace, then applying a pressure of 60 MPa, heating to 750° C. and keeping the temperature for 10 minutes, and finally cooling to 150° C.;
[0085] The heating rate in the integrated hot pressing sintering step is 120°C / min and the cooling rate is 20°C / min;
[0086] The mass of the barrier layer powder is 20% of the skutterudite powder;
[0087] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0088] The electrode is a Cu electrode;
[0089] The grinding method is to grind with 800 mesh, 1500 mesh and 3000 mesh sandpaper in sequence; the polishing method is to polish with a diamond polishing agent with a particle size of 2.5 μm on a polishing cloth; the cleaning method is to rinse with anhydrous ethanol, then ultrasonically clean in anhydrous ethanol for 10 minutes, and finally air-dry;
[0090] The solder is CuSnP solder; CuSnP solder is a commercial solder with a liquidus temperature of 600-700°C;
[0091] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, the temperature was increased to 675 °C at a heating rate of 10 °C / min for 10 min, and then decreased to 200 °C at a rate of 5 °C / min.
[0092] Figure 3 Yb in the brazed joint obtained in Example 3 0.3 4Sb 12 The interface structure photo with the CoMo barrier layer. The CoMo barrier layer can also be used to obtain a joint with good barrier effect and no cracks or holes, indicating that the present invention has universal applicability in the field of thermoelectric material connection technology.
[0093] After testing, the Yb 0.3 4Sb 12 The shear strength of the brazed joint of the thermoelectric device is 32.0MPa, which meets the mechanical property requirements of the thermoelectric device.
[0094] Example 4
[0095] The method of this embodiment using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0096] Step 1: Put Co powder and Mo powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0097] The mass ratio of the Co powder to the Mo powder is 6:4;
[0098] The ball milling step is as follows: Co powder, Mo powder, grinding balls and anhydrous ethanol are placed in a ball milling jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then the ball milling is carried out for 12 hours under an atmospheric environment, and the ball milling is carried out after the ball milling is completed, and the ball milling is carried out in a drying oven for drying;
[0099] Step 2: Yb 0.3 4Sb 12 The powder is poured into a graphite mold and then 0.3 4Sb 12 A layer of barrier layer powder is spread on the powder, and then the powder is transferred to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a pre-set barrier layer;
[0100] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 0.5 kPa, then filling argon gas to a pressure of 80 kPa in the hot pressing furnace, then applying a pressure of 60 MPa, heating to 750° C. and keeping the temperature for 10 minutes, and finally cooling to 150° C.;
[0101] The heating rate in the integrated hot pressing sintering step is 120°C / min and the cooling rate is 20°C / min;
[0102] The mass of the barrier layer powder is 20% of the skutterudite powder;
[0103] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0104] The electrode is a Cu electrode;
[0105] The grinding method is to grind with 800 mesh, 1500 mesh and 3000 mesh sandpaper in sequence; the polishing method is to polish with a diamond polishing agent with a particle size of 2.5 μm on a polishing cloth; the cleaning method is to rinse with anhydrous ethanol, then ultrasonically clean in anhydrous ethanol for 10 minutes, and finally air-dry;
[0106] The solder is CuSnP solder; CuSnP solder is a commercial solder with a liquidus temperature of 600-700°C;
[0107] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, the temperature was increased to 675 °C at a heating rate of 10 °C / min for 10 min, and then decreased to 200 °C at a rate of 5 °C / min.
[0108] After testing, the Yb 0.3 4Sb 12 The shear strength of the welded joint of the thermoelectric device is 26.9MPa, which meets the mechanical performance requirements of the thermoelectric device.
[0109] Example 5
[0110] The method of this embodiment using a cobalt-based barrier layer to improve the strength and long-term service performance of the brazed joint in a skutterudite thermoelectric device is carried out in the following steps:
[0111] Step 1: Put Co powder and Mo powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder;
[0112] The mass ratio of the Co powder to the Mo powder is 7:3;
[0113] The ball milling step is as follows: Co powder, Mo powder, grinding balls and anhydrous ethanol are placed in a ball milling jar, so that the anhydrous ethanol just covers the powder and the grinding balls, and then the ball milling is carried out for 12 hours under an atmospheric environment, and the ball milling is carried out after the ball milling is completed, and the ball milling is carried out in a drying oven for drying;
[0114] Step 2: Yb 0.3 4Sb 12 The powder is poured into a graphite mold and then 0.3 4Sb 12 A layer of barrier layer powder is spread on the powder, and then the powder is transferred to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a pre-set barrier layer;
[0115] The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 0.5 kPa, then filling argon gas to a pressure of 80 kPa in the hot pressing furnace, then applying a pressure of 60 MPa, heating to 750° C. and keeping the temperature for 10 minutes, and finally cooling to 150° C.;
[0116] The heating rate in the integrated hot pressing sintering step is 120°C / min and the cooling rate is 20°C / min;
[0117] The mass of the barrier layer powder is 20% of the skutterudite powder;
[0118] Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing;
[0119] The electrode is a Cu electrode;
[0120] The grinding method is to grind with 800 mesh, 1500 mesh and 3000 mesh sandpaper in sequence; the polishing method is to polish with a diamond polishing agent with a particle size of 2.5 μm on a polishing cloth; the cleaning method is to rinse with anhydrous ethanol, then ultrasonically clean in anhydrous ethanol for 10 minutes, and finally air-dry;
[0121] The solder is CuSnP solder; CuSnP solder is a commercial solder with a liquidus temperature of 600-700°C;
[0122] The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, the temperature was increased to 650 °C at a heating rate of 10 °C / min for 10 min, and then decreased to 200 °C at a rate of 5 °C / min.
[0123] After testing, the Yb 0.3 4Sb 12 The shear strength of the brazed joint of the thermoelectric device is 30.1MPa, which meets the mechanical performance requirements of the thermoelectric device.
Claims
1. A method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices by using a cobalt-based barrier layer, characterized in that: The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer is carried out in the following steps: Step 1: Put cobalt powder and refractory metal powder into a ball mill for ball milling, and mix them evenly to obtain barrier layer powder; The barrier layer powder is formed by mixing cobalt powder and refractory metal powder, and the mass fraction of the cobalt powder in the barrier layer powder is 50% to 98%; The refractory metal powder is one or more of tungsten powder, molybdenum powder, niobium powder and tantalum powder; Step 2: pouring the skutterudite powder into a graphite mold, then spreading a layer of barrier layer powder on the skutterudite powder, and then transferring it to a hot pressing furnace for integrated hot pressing sintering to obtain skutterudite with a preset barrier layer; The integrated hot pressing sintering step is: evacuating the hot pressing furnace to a pressure less than 1 kPa, then filling argon gas to a pressure of 50 to 100 kPa in the hot pressing furnace, then applying a pressure of 50 to 70 MPa, heating to 700 to 800° C. and keeping the temperature for 5 to 20 minutes, and finally cooling to 100 to 200° C.; Step 3: grinding, polishing and cleaning the barrier layer surface in the skutterudite with a preset barrier layer and the surface to be welded of the electrode in sequence, and then placing a brazing material between the barrier layer in the skutterudite with a preset barrier layer and the surface to be welded of the electrode for brazing; The solder is a Cu-based solder; The brazing process is as follows: the vacuum pressure of the vacuum furnace is less than 5×10 -3 Pa, heat up to 600-700°C at a heating rate of 5-20°C / min for 5-20min, and then decrease to 100-200°C at a rate of 2-10°C / min.
2. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: The ball milling step in step 1 is as follows: cobalt powder, refractory metal powder, grinding balls and anhydrous ethanol are loaded into a ball mill jar so that the anhydrous ethanol just covers the powder and the grinding balls, and then ball milled in an atmospheric environment for 6 to 24 hours. After the ball milling is completed, the ball mill is placed in a drying oven for drying.
3. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: The chemical formula of the skutterudite in step 2 is R x Co y Fe 4-y Sb 12 , R is one or more of alkali metals, alkaline earth metals, rare earth metals, and elements of the third main group, 0<x≤1, 0≤y≤4.
4. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: In the integrated hot pressing sintering step of step 2, the heating rate is 80-150° C. / min, and the cooling rate is 5-50° C. / min.
5. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: In step 2, the mass of the barrier layer powder is 5% to 25% of the skutterudite powder.
6. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: In step 3, the electrode is a metal electrode or an alloy electrode.
7. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 6, characterized in that: The metal electrode is made of Cu, Ni, Fe, Co or Cr.
8. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 6, characterized in that: The alloy electrode is a Cu-based alloy, a Ni-based alloy, a Fe-based alloy, a Co-based alloy or a Cr-based alloy.
9. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 6, characterized in that: The Cu-based alloy is CuW or CuMo; the Ni-based alloy is NiW, NiMo or NiCr; the Fe-based alloy is FeW, FeMo, FeCr or FeCoNi; the Co-based alloy is CoW, CoMo, CoCr, CoNi or CoFe; and the Cr-based alloy is CrW, CrMo, CrCoNi or CrFeNi.
10. The method for improving the strength and long-term service performance of brazed joints in skutterudite thermoelectric devices using a cobalt-based barrier layer according to claim 1, characterized in that: The grinding method in step 3 is to grind step by step with 800-3000 mesh sandpaper; the polishing method is to polish on a polishing cloth with a diamond polishing agent with a particle size of 0.5-2.5 μm; the cleaning method is to rinse with acetone or anhydrous ethanol, then ultrasonically clean in acetone or anhydrous ethanol for 5-30 minutes, and finally air-dry.
Citation Information
Patent Citations
Diffusion welding method for connecting skutterudite and electrode through high-entropy alloy intermediate layer
CN113828906A
Method for connecting skutterudite thermoelectric material with Fe-Cr-Mo / W as barrier layer and copper electrode
CN115415656A
Method for connecting skutterudite thermoelectric material and electrode by using surface-roughened barrier layer
CN115955901A
Method for brazing and connecting skutterudite and copper electrode by using copper-tin-phosphorus brazing filler metal
CN116475700A
Display Device
KR1020220005199A
Cited By
Skutterudite thermoelectric material / electrode high-thermal-stability welding method based on metal ceramic composite barrier layer
CN119952173A
A high-thermal-stability welding method for skutterudite thermoelectric material / electrode based on a cermet composite barrier layer
CN119952173B